IMPLEMENTASI ALAT PERAGA BERBASIS METODE MONTESSORI PADA PEMBELAJARAN MATEMATIKA MATERI PERKALIAN KELAS II MI GUPPI AT-TAQWA KALIWADER - KHALIMATUS SAKDIYAH; Dhiya Ayu Tsamrotul Ihtiari (As-Sibyan, 2021)
This study aims to: 1) describe the implementation of the Montessori method based teaching aids in mathematics learning materials of multiplication class II MI Guppi At-Taqwa Kaliwader. 2) to describe the impact of the implementation of the Montessori method based teaching aids on mathematics learning in class II MI Guppi At-Taqwa Kaliwader on student attitudes and learning outcomes. The type of research used is descriptive qualitative. The subjects of this study were students of class II MI Guppi At-Taqwa Kaliwader. While the object of this study is a props based on the Montessori method for multiplication count operations with thee concept of repeated addition. Data collection in this study was carried out by means of observation and tests. The results of this study are in the form of descriptions of the results of the implementation of teaching aids based on the Montessori method in mathematics learning materials for the multiplication of class II MI Guppi At-Taqwa Kaliwader. The impact of the implementation of the Montessori method based teaching aids on the learning of class II multiplication material at MI Guppi At-Taqwa Kaliwader showed positive results, namely the first meeting showed a class average of 90,45. Meanwhile, at the second meeting, it showed an average og 90,90 in the every high category.